Relative age effect in French alpine skiing : problem and solution - Delarochelambert, Q. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: The objective of this study is to identify the potential bias of the relative age effect (RAE) in French alpine skiers and to propose a mathematical correction adjustment for such bias.